Can "the whole world" be wrong? : lethal journalism, antisemitism, and global jihad - Landes, Richard, 1949- (Antisemitism in America., 2022)
"Drawing on the dynamics of apocalyptic movements (outrageous energizing hopes, aggressive denial when disappointed), Landes looks at the turn of the millennium (2000) in terms of a radical mismatch between two millennial styles, an Islamist pre-modern (Caliphators) and a Western post-modern (Woke). Due to a striking cognitive failure, Westerners could neither see nor discuss the foe they faced, and repeatedly, convinced they were bending the arc of history towards justice, took sharp wrong turns. We continue to do so"--